2019
DOI: 10.1002/1873-3468.13584
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial dysfunction increases fatty acid β‐oxidation and translates into impaired neuroblast maturation

Abstract: The metabolic transition from anaerobic glycolysis and fatty acid β‐oxidation to glycolysis coupled to oxidative phosphorylation is a key process for the transition of quiescent neural stem cells to proliferative neural progenitor cells. However, a full characterization of the metabolic shift and the involvement of mitochondria during the last step of neurogenesis, from neuroblasts to neuron maturation, is still elusive. Here, we describe a model of neuroblasts, Neuro2a cells, with impaired differentiation cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 49 publications
3
13
0
Order By: Relevance
“…These changes were associated with defective mitochondrial ultrastructure ( Figure S1B) and reduction of ETC complex subunits (Smestad et al, 2018a). This correlation is consistent with prior reports linking ETC dysfunction with increased fatty acid oxidation (FAO) (Chen et al, 2018;Vazquez et al, 2015) and accumulation of acyl-carnitines (Audano et al, 2019), and may be related to the known physical association of FAO enzymes with ETC complexes (Wang et al, 2010;Wang et al, 2019b).…”
Section: Tca Cycle Disruption Causes a Protein Pan-hyperacylation Phesupporting
confidence: 89%
“…These changes were associated with defective mitochondrial ultrastructure ( Figure S1B) and reduction of ETC complex subunits (Smestad et al, 2018a). This correlation is consistent with prior reports linking ETC dysfunction with increased fatty acid oxidation (FAO) (Chen et al, 2018;Vazquez et al, 2015) and accumulation of acyl-carnitines (Audano et al, 2019), and may be related to the known physical association of FAO enzymes with ETC complexes (Wang et al, 2010;Wang et al, 2019b).…”
Section: Tca Cycle Disruption Causes a Protein Pan-hyperacylation Phesupporting
confidence: 89%
“…Mitochondrial ROS production is directly dependent on mitochondrial function and an increase of this parameter has been linked to the OA pathogenesis [46]. Furthermore, it has also been suggested that mitochondrial dysfunction induces FA oxidation and oxidative stress [47][48][49]. Thus, this study may confirm the role of mitochondrial dysfunction in OA as seen by the results from OA cybrids with preference of FAs for oxidation and increased ROS production.…”
Section: Discussionsupporting
confidence: 76%
“…Given the close relationship between physiological and/or pharmacological external cues and the impact on the systemic metabolic profile, this experimental approach has been extensively used in nutrition, 72,73 agricultural, 74,75 dairy, 76,77 toxicology, 78,79 preclinical, and clinical studies. In life sciences, targeted metabolomics has been mainly employed for the characterization of known metabolites and pathways (i.e., amino acids, glycolysis, Krebs cycle, and pentose phosphate pathway) in in vitro, ex vivo, and in vivo experimental settings 6,80–90 . On the other hand, untargeted metabolomics is mainly used for the identification of biomarkers in biomedical research, for instance, in pathophysiology (i.e., cancer, 91 neurodegenerative diseases, 92,93 and metabolic disorders 94 ) or epidemiology studies 95,96 .…”
Section: Main Applications Of Steady‐state Metabolomicsmentioning
confidence: 99%